Transforming Customary Land Into Sustainable Economic Assets Through Waqf Funds and Islamic Bank Support - Rahmah, Azizatur; Siregar, Erni Yusnita (STAI Serdang Lubuk Pakam, 2025)
This study aims to explore a model for transforming customary land into productive economic assets through waqf funding and Islamic banking. This approach is expected to create synergy between sharia principles and regional economic development. Using a case study with qualitative methods, the results show that the utilization of customary land through a productive waqf scheme supported by Islamic banking has great potential as a sustainable economic asset. This scheme provides a positive return on investment for indigenous communities, increases household income, and strengthens the regional economy. The main challenges are related to indigenous land regulations and community understanding of the concept of productive waqf. However, collaboration between waqf institutions, Islamic banks, and the government has proven effective in overcoming these obstacles. These findings confirm that transforming customary land with waqf funds and Islamic financing can support the sustainable well-being of indigenous communities, enhance economic self-reliance, and reduce dependence on external aid. More supportive education and regulations are needed for the effective and sustainable implementation of this model.